A Coupled Eulerian Lagrangian (CEL) Model in Prediction Tool Temperature - Zakaria, M.S. (Springer Science and Business Media Deutschland GmbH, 2021)
In this paper, modelling technique of predicting cutting temperature by using commercial FEM code ABAQUS is discussed. A considered 2D plain strain orthogonal cutting of AZ31 Mg alloy with coupled Eulerian Lagrangian model is deployed to simulate cutting process. The JohnsonâCook constitutive model is employed to describe material behavior undergo severe plastic deformation during cutting. Generally, this study is to enlighten temperature distribution at rake surface. The numerical model is validated to previous experiment data and a good agreement is achieved. It is found temperature is high near the cutting edge and heat is distributed at rake face from contact between chip and tool. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.